Sikap Mahasiswa terhadap Penggunaan Bahasa Ibu dalam Pembelajaran Bahasa Arab pada Prodi Pendidikan Bahasa Arab - Arifudin Arifudin (STIQ Amuntai, 2025)
The use of the mother tongue in learning Arabic has a negative impact. This negative impact is an obstacle to the effectiveness of learning Arabic. This research aims to determine the attitudes of PBA Study Program students towards the use of their mother tongue in learning Arabic. Apart from that, to find out the impact of its use according to students. This research is a quantitative descriptive study with a population of all active students of the IAIN Pontianak Arabic Language Education Study Program. The sample was determined using random sampling techniques. The results of this research indicate that the mother tongue is used in learning Arabic in the PBA Study Program. PBA Study Program students do not yet have a completely positive attitude in using Arabic in learning. However, students understand that using Arabic as the language of instruction in learning Arabic has a very positive impact. Using appropriate learning methods will be a solution to the problem of low mastery of Arabic for students.